Image Findings of Acute to Subacute Craniocervical Arterial Dissection on Magnetic Resonance Vessel Wall Imaging: A Systematic Review and Proportion Meta-Analysis - Cho, Se Jin; Choi, Byung Se; Bae, Yun Jung; Baik, Sung Hyun; Sunwoo, Leonard; Kim, Jae Hyoung (Frontiers in Neurology, 2021)
Background and Purpose: To evaluate the pooled proportion of image findings of acute to subacute craniocervical arterial dissection (AD) direct signs on magnetic resonance-vessel wall imaging (MR-VWI) and to identify factors responsible for the heterogeneity across the included studies. Methods: A systematic literature search in the Ovid-MEDLINE and EMBASE databases was performed for studies published on the relevant topic before April 14, 2020. Pooled sensitivity and specificity values and their 95% confidence intervals (CIs) were calculated using bivariate random-effects modeling. Meta-regression analyses were also performed to determine factors influencing heterogeneity. Results: Eleven articles with data for 209 patients with acute to subacute craniocervical AD who underwent MR-VWI were included in this systematic review and meta-analysis. The most common findings on MR-VWI were wall hematoma (84%; 95% CI, 71–92%), abnormal enhancement (72%; 95% CI, 49–88%), aneurysmal dilatation (71%, 95% CI, 53–84%), and intimal flap or double lumen signs (49%; 95% CI, 29–71%). Among the potential covariates of heterogeneity, the presence of contrast enhanced T1-weighted imaging (CE-T1WI) within the MR-VWI sequence combination significantly affected the pooled proportion of the intimal flap or double lumen signs. Conclusion: Wall hematoma and intimal flap or double lumen signs were the most common and least common direct sign image findings, respectively, on MR-VWI in patients with acute to subacute craniocervical AD. Furthermore, it is recommended that CE-T1WI be included in MR-VWI sequences for protocol optimization. This data may help improve MR-VWI interpretation and to enhance the understanding of the radiologic diagnosis of craniocervical AD.